A day in the life of a biopharmaceutical senior scientist. (3rd February 2021) - Unknown
Abstract : Dr Jana Broecker is a senior scientist in the Biochemistry Department at Sosei Heptares in the UK, where she is part of a team that develops small-molecule therapeutics using protein structural information. Jana graduated as a Diploma Engineer from the Technical University Berlin (Germany) and did her PhD with the University of Kaiserslautern on the biophysical quantification of membrane-protein stability. She also completed post-doctoral research at the University of Toronto (Canada), where she spearheaded the optimization of membrane-protein crystallization using polymer-bound lipid nanodiscs and where she also developed a method that avoids crystal harvesting.